Enhancing Students’ Fraction Comparison Skills Through Teacher Development - SVEIDER, Cecilia; SAMUELSSON, Joakim (Journal of Research in Educational Sciences; Vol 16 No 2 (2025): JRES, Volume XVI, Issue 2(20), Winter 2025DO - 10.14505/jres.v16.2(20).07, 2025)
This study investigates the effects of a professional development (PD) program for mathematics teachers on improving the teaching of fractions, with a particular focus on fraction comparison. The study aims to examine how continuous, structured PD can enhance both teachers’ instructional practices and students’ learning outcomes. Four middle school teachers and 130 students participated in a year-long intervention, consisting of seven cycles of planning, teaching, and reflection. Student performance was assessed using tasks measuring comparison and ordering of fractions, and results were compared with a control group. Teachers’ experiences and reflections were collected through observations and self-reports. Students in the intervention group showed significant improvement in comparing and ordering fractions compared to the control group. The most notable gains were observed in tasks involving comparison with reference points and proximity to reference points. Teachers reported increased awareness of the structure of teaching materials, adoption of more methodical teaching strategies, and enhanced reflection on instructional design. The study shows that long-term, focused PD with structured methods leads to measurable improvements in teaching and enhances students’ conceptual understanding of fractions, highlighting the importance of sustained, targeted teacher support. The study is limited by the small number of participating teachers, which may affect generalizability. Further research could investigate larger samples and different grade levels. The results suggest that school leaders should consider long-term, iterative PD programs with structured cycles to support teacher development and student achievement.